Colon Lipoma Causing Colo-Colic Intussusception in an Adult: A Case Report from Tanzania - Jamil Suleiman; Mujaheed Suleman; Alex Mremi; Adnan Sadiq; Abbas Mohamedali; Dennis Machaku; Jay Lodhia (Case Reports in Surgery)
Intussusception is rarely seen in adulthood but is commonly seen in the pediatric age group. Causes of intussusception in adults are commonly due to tumors and inflammatory diseases. Intussusception in adults accounts for less than 5% of intestinal obstruction. Colonic lipomas are usually asymptomatic and are mostly managed surgically with promising outcomes as seen in our case.